Atypical Manifestations in Glut1 Deficiency Syndrome. (August 2016) - De Giorgis, V.; Varesio, C.; Baldassari, C.; Piazza, E.; Olivotto, S.; Macasaet, J.; Balottin, U.; Veggiotti, P.
Glucose transporter type 1 deficiency syndrome is a genetically determined, treatable, neurologic disorder that is caused by an insufficient transport of glucose into the brain. It is caused by a mutation in the SCL2A1 gene, which is so far the only known to be associated with this condition. Glucose transporter type 1 deficiency syndrome consists of a wide clinical spectrum that usually presents with cognitive impairment, epilepsy, paroxysmal exercise-induced dyskinesia, acquired microcephaly, hemolytic anemia, gait disturbance, and dyspraxia in different combinations. However, there are other clinical manifestations that we consider equally peculiar but that have so far been poorly described in literature. In this review, supported by a video contribution, we will accurately describe this type of clinical manifestation such as oculogyric crises, weakness, paroxysmal kinesigenic and nonkinesigenic dyskinesia in order to provide an additional instrument for a correct, rapid diagnosis.